Tenure security under the Communal Property Associations Act 28 of 1996 : an analysis of establishment and management procedures with comparative reference to the Sectional Titles Act 95 of 1986 - Jacobs, Petrus Jacobus (Stellenbosch : University of Stellenbosch, 2011)
Thesis (LLM )-- University of Stellenbosch, 2011.